2015
DOI: 10.4238/2015.september.9.7
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of silicosis with hepatocyte growth factor-modified autologous bone marrow stromal cells: a non-randomized study with follow-up

Abstract: ABSTRACT. Pulmonary silicosis is an irreversible and untreatable disease that is characterized by interstitial lesions and perpetual fibrosis in the lungs. This study was performed to determine whether mesenchymal stem cells (MSCs) and hepatocyte growth factor (HGF) could exhibit therapeutic effects on human silicosis. This nonrandomized uncontrolled trial comprised four patients with pulmonary silicosis who had developed lung fibrosis and received autologous bone marrow MSCs previously transfected by a vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…The marked data were used in meta-analysis. For case series [12, 1517, 20, 21, 23, 27, 31], we combined individual data using the formulas, Xtrue¯=xn and italicSD=(xtruex¯)2n1, where x stands for variance, trueX¯ is the mean of pooled individual data, and n is the sample size. To combine data of subgroups, mean and SD were computed with these equations: italicmean=N1M1+N2M2N1+N2 and SD=(N11)SD12+(N21)SD22+N1N2N1+N2(M12+M222M1M2)N1+N21, where N and M represent the size and mean of subgroup, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The marked data were used in meta-analysis. For case series [12, 1517, 20, 21, 23, 27, 31], we combined individual data using the formulas, Xtrue¯=xn and italicSD=(xtruex¯)2n1, where x stands for variance, trueX¯ is the mean of pooled individual data, and n is the sample size. To combine data of subgroups, mean and SD were computed with these equations: italicmean=N1M1+N2M2N1+N2 and SD=(N11)SD12+(N21)SD22+N1N2N1+N2(M12+M222M1M2)N1+N21, where N and M represent the size and mean of subgroup, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that the HGF/c-Met signaling pathway is associated with malignant cancers, and may be involved with cancer metastasis (Anderson et al, 2006). Conversely, recent studies have shown that HGF may exhibit therapeutic effects on some diseases such as human silicosis (Liu et al, 2015) and myocardial ischemic injury (Wang et al, 2014). The possible role of HGF and CK18 in the development and progression of ESCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Other antifibrotic agents including tadalafil are also being trialled in animal models. 90 Cell-based therapy including bone marrow-derived mononuclear cell 91 and mesenchymal cell transplantation 92 have both demonstrated some benefit in animal models and are currently undergoing trials in humans. 93…”
Section: Antifibrotic Therapymentioning
confidence: 99%